Remuneration Committee and Cost of Equity Capital: A Study of Manufacturing Companies on the Indonesia Stock Exchange for the Period 2013-2023 - Darwis, Herman; Gumati, Tatang Ary; Arifin, Andi Harmoko; Rita, Maria Rio (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2025)
This study aims to examine the effect of the remuneration committee on the cost of equity capital. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2023. The data collection procedure used purposive sampling, the sample used companies that formed a remuneration committee, the number of observations used in this study from 2013 to 2023 was 371, with a sample size of 38 companies. The data analysis technique used multiple linear regression panel data. This study enriches the corporate governance literature in Indonesia with a comprehensive approach to measuring the cost of capital. The results found that the remuneration committee was found to be significantly negatively related to the cost of equity capital. This means that the existence of a remuneration committee is associated with a decrease in the cost of equity capital. This finding confirms that the formation of a remuneration committee can help monitor and advise executive management regarding remuneration decisions. The control variable of company size has a significant negative effect on the cost of equity capital. The control variables of sales growth, debt, and earnings quality do not affect the cost of equity capital.